Implementation of water conservation programs - Silva, Gisele Sanches da (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
This research work proposes a methodology for implementing water conservation programs in university campi. The planning – motivation, aims, preliminary diagnosis of the situation and structure – of this kind of program must be carried out before the implementation of activities. Then, it is necessary to define priorities, to make the necessary contacts with university units and companies (pre-implementation) and to carry out the actual stages of implementation: making an in-depth diagnosis; physical loss reduction; reduction of consumption in water use points; characterization of habits and rationalization of activities that consume water; and program dissemination, including awareness campaigns and training. In the post-implementation stage, some of these activities must be kept, as well as the water demand management – besides the data survey that includes the determination of control parameters and the definition of intervention procedures on the systems whenever there are anomalies. The Water Conservation Program at the University of São Paulo is presented, both the implementation and results. This program achieved, from 1998 to 2003, 36% of water consumption reduction (from 137,881 to 88,366 m³/month) and resulted in an net economic benefit of US$ 16.13 millions (R$ 46.61 millions).